Understanding beneficiary satisfaction through logistics efficiency and digital technology in Indonesia's free nutritious meal program - Vinanda Vinanda; Tien Yustini (Jurnal Mantik, 2026)
High malnutrition rates among pregnant women, infants, and children pose a significant challenge to Indonesia's human resource development and the "Indonesia Emas 2045" vision. To address this, the government initiated the Free Nutritious Meals Program (Makanan Bergizi Gratis / MBG). However, operational bottlenecks such as inefficient distribution, underutilized technology, and inconsistent service quality-persist. This study examines the impact of logistics distribution efficiency, information technology utilization, and service quality on beneficiary satisfaction within the MBG program. Using a quantitative approach, data were gathered from 294 respondents at SMAN 14 Palembang (selected via purposive sampling using Slovin’s formula from a population of 1,105) through structured Likert-scale questionnaires. Analysis was conducted using SPSS, incorporating validity, reliability, classical assumption tests, and multiple linear regression. The findings demonstrate that logistics distribution efficiency, information technology, and service quality both individually and collectively have a positive and statistically significant effect on beneficiary satisfaction. By empirically evaluating these core operational drivers, this study offers actionable insights for program administrators to optimize distribution channels, integrate digital management tools, and refine service delivery across national meal programs